Enhancing Fine and Gross Motor Skills through Innovative Plant-Themed Worksheets: A Development Research at TKK Kemala Bhayangkari 08 Bajawa - Maku, Karmelia Rosfinda Meo; Nafsia, Andi; Meo, Lidia (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aimed to develop and validate plant-themed children’s worksheets (LKA) specifically designed to stimulate the physical and motor development of early childhood students. This study addresses the gap in available teaching materials at TKK Kemala Bhayangkari 08 Bajawa, which previously relied on generic, non-contextual resources that were less effective in engaging children's active movement and coordination. Method: This study employed a Research and Development (R&D) approach using the 4-D development model: Define, Design, Develop, and Disseminate. Data were collected through expert validation (media, content, and learning design specialists), teacher interviews, and direct observations. The feasibility of the product was measured using Likert-scale questionnaires, and its effectiveness was evaluated by comparing children's motor skill performance before and after the implementation of the developed LKA. Results: The findings indicate that the plant-themed LKA is highly feasible and effective. The expert validation scores reached an average of 3.38 (good/valid category). The implementation results showed a significant improvement in children's physical-motor abilities, with fine motor skills increasing by 25% and gross motor skills by 29%. Furthermore, the media received high practicality ratings from teachers (95%) and parents (90%), who noted increased student engagement owing to the contextual nature of the plant-based activities. Novelty: This study contributes to early childhood education by providing a context-based LKA that integrates local environmental themes (plants) with specific physical-motor exercises. Unlike standardised worksheets, this developed media bridges the gap between cognitive understanding of nature and physical activity, offering a replicable model for teachers in rural or specific ecological regions to develop localised teaching aids for children.